2019
DOI: 10.5539/jas.v11n6p191
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Potential Pollinizer Grafted Pear Hybrids (Pyrus communis × Pyrus pyrifolia) for Subtropical Regions in Brazil

Abstract: The pear tree is originally a temperate-climate fruit tree. The cross Pyrus communis × Pyrus pyrifolia generated hybrid cultivars adapted to subtropical regions. However, the low effective fruiting is a limiting factor for the expansion of pear tree crops in subtropical regions and no pollinizer plants have been identified for these cultivars in subtropical regions. This work aimed to identify possible pollinizer pear tree cultivars in subtropical regions by evaluating the stigmatic receptivity, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 11 publications
0
8
1
Order By: Relevance
“…This result demonstrates that controlled crosses of these cultivars can be performed before the opening of the flower in genetic improvement programs. However, Bisi et al (2019b) found a shorter period of stigmatic receptivity than done here, which may be due to the high temperatures reported by those authors. Stigmatic receptivity is a key factor in the assessment of compatibility between cultivars, as the suitability of flowers in the fertilization process is directly related to their receptivity to pollen grain (Zambon et al 2018).…”
Section: Resultscontrasting
confidence: 72%
See 4 more Smart Citations
“…This result demonstrates that controlled crosses of these cultivars can be performed before the opening of the flower in genetic improvement programs. However, Bisi et al (2019b) found a shorter period of stigmatic receptivity than done here, which may be due to the high temperatures reported by those authors. Stigmatic receptivity is a key factor in the assessment of compatibility between cultivars, as the suitability of flowers in the fertilization process is directly related to their receptivity to pollen grain (Zambon et al 2018).…”
Section: Resultscontrasting
confidence: 72%
“…All stages of reproductive development showed the formation of bubbles in the stigma cavity when subjected to the 3% hydrogen peroxide test, indicating the activity of the peroxidase enzyme. Bisi et al (2019b) observed 100% receptivity in the stages after floral anthesis and in the balloon stage (preanthesis) in the cultivars 'Seleta' , 'Tenra' , and 'Triunfo' . This result demonstrates that controlled crosses of these cultivars can be performed before the opening of the flower in genetic improvement programs.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations